Extragastrointestinal Stromal Tumor during Pregnacy - Ilay Gözükara; T. U. Kutlu Dilek; Hüseyin Durukan; Duygu Düsmez Apa; Suna Kabil Kucur; Saffet Dilek (Hindawi Limited, 2012)
Extragastrointestinal stromal tumors (EGISTs) are mesenchymal neoplasms without connection to the gastrointestinal tract. Gastrointestinal stromal tumors (GISTs) and EGIST are similar according to their clinicopathologic and histomorphologic features. Both of them most often express immunoreactivity for CD-117, a c-kit proto-oncogene protein. The coexistence of GIST and pregnancy is very rare, with only two cases reported in the literature. In this paper, we presented the first EGIST case during pregnancy in the literature.